Implementation of Service Quality to Increase Customer Satisfaction at Arascarf in Malang City - Nur Afika Fitriani; Yaumi Rohmah; Sudarmiatin Sudarmiatin (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2025)
This study aims to analyze the implementation of service quality to improve customer satisfaction at Arascarf MSMEs in Malang City. The researcher uses the SERVQUAL model as an analytical framework to evaluate five dimensions of service quality, namely physical evidence, reliability, responsiveness, assurance, and empathy. This study was conducted with a qualitative case study approach. The researcher obtained data through in-depth interviews, direct observation, and documentation. The researcher found that the dimensions of responsiveness and empathy have a dominant influence on positive consumer perceptions. Consumers consider that fast service and friendly attitudes from MSMEs create a sense of comfort and trust. However, the researcher also found that in the dimensions of physical evidence and assurance, there are still shortcomings that need to be fixed. Overall, consumer attitudes towards Arascraf services are positive, but still require improvement in aspects of professionalism and quality consistency. This study concludes that strengthening the five dimensions of SERVQUAL in a balanced manner can be an effective strategy to build customer satisfaction and loyalty sustainably.